Análise da estrutura filogeográfica das espécies do grupo Pilosocereus Aurisetus (Cactaceae) utilizando marcadores moleculares do genoma do cloroplasto (cpDNA) - Bonatelli, Isabel Aparecida da Silva (Universidade Federal de São Carlos, 2012)
PILOSOCEREUS AURISETUS is a taxonomic group composed by eight columnar cacti species occurring on rock outcrops in xeric environments. As other xerophitic species found outside the Caatinga domain, the species populations of P. AURISETUS group exhibit a disjunct distribution pattern within the Cerrado domain in central and eastern Brazil. Such a distribution pattern may have resulted from long-distance dispersal events or fragmentation of a more extensive distribution in the past. The main goal of this work was identify demographic events that possibly shaped the evolutionary history of the group and resulted in the current biogeographic pattern. In the present work, phylogenetic analyses and phylogeographical inferences were implemented using the nucleotide variation of plastid genomic sequences. The phylogenetic analyses showed the absence of reciprocal monophyly for great part of the species and the occurring of quite divergent species from the others of the group: P. jauruensis, P. aureispinus e P. bohlei. In addition, P. machrisii populations formed two distinct clades highly supported by the phylogeny which partly agree with the geographic distribution of the species (north and central-south). Population analyses and phylogeographical inferences allowed the identification of the diversification origin of the group and the possible expansion and fragmentation events which determined the evolutionary pathway of the populations. The genetic variability level and the genetic structure observed alongside the current distribution pattern of the populations and biological information about the species suggest that fragmentation events were the main responsible for the biogeographical pattern of the group, which should be related to the palioclimatic oscillations of the Quaternary.
Keywords: Filogeografia; Filogenia; Genoma plastidial; Pilosocereus; Cactaceae; Phylogeography; Phylogeny; Plastid genome; Pilosocereus; Cactaceae; CIENCIAS BIOLOGICAS::GENETICA